2007
DOI: 10.5507/bp.2007.041
|View full text |Cite
|
Sign up to set email alerts
|

Use of glycogen phosphorylase BB measurement with POCT in the diagnosis of acute coronary syndromes. A comparison with the ELISA method

Abstract: Key words: Acute coronary syndrome/Myocardial ischemia/Non-STEMI/Coronary by-pass/Laboratory markers of myocardial ischemia/CAD/GPBB/POCT/ELISABackground: Glycogen Phosphorylase BB (GPBB) is considered an early and specifi c marker of myocardial necrosis and ischemia. A POCT kit GPBB for diagnostic use has recently been approved.Aim: an evaluation of the correspondence of qualitative POCT GBPP measurements with ELISA test results. Material and methodology: 20 individuals with non-ST elevation myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…H-FABP and GPBB are newer perspective markers for the early detection of myocardial ischemia and necrosis, recently evaluated in the diagnostics and risk stratification of acute coronary syndromes [68][69][70][71] . H-FABP is a relatively small cytoplasmic protein for the oxidation of fatty acids that is quite specific for cardiac muscle.…”
Section: Perspective Markers Of Ct-induced Cardiotoxicity (Under Study)mentioning
confidence: 99%
“…H-FABP and GPBB are newer perspective markers for the early detection of myocardial ischemia and necrosis, recently evaluated in the diagnostics and risk stratification of acute coronary syndromes [68][69][70][71] . H-FABP is a relatively small cytoplasmic protein for the oxidation of fatty acids that is quite specific for cardiac muscle.…”
Section: Perspective Markers Of Ct-induced Cardiotoxicity (Under Study)mentioning
confidence: 99%
“…[11,18] The early release of GPBB into the blood is a common result of the combination with of escalated glycogenolysis and increased permeability of cell membranes which is typical for myocardial ischemia and necrosis. [12,13,19] In this study, we found that GPBB was the most sensitive and specific biomarker to detect myocardial infarction when compared to MB and CKMB at the first 4 h ( Table 2). This finding is in agreement with Rabitzsch et al [20] and Cubranic et al [21] who also reported the highest sensitivity of GPBB in the early hours of chest pain.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, GPBB which is connected to glycogen in a macromolecular complex that is structurally bound to sarcoplasmic reticulum believes to release from glycogen and then enters the bloodstream via the T-tubulus system within 1-4 ho of onset of AMI. [11][12][13] Hence, this study has been aimed to compare the sensitivity and specificity of GPBB with those of MB and CKMB within 4 h after the onset of chest pain.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of a biomarker is determined by diagnostic accuracy and convenience. The availability of a point-of-care platform that allows for rapid and simultaneous measurement of GPBB and cardiac troponins facilitates the frontline clinician’s ability to make timely management decisions 29. Overall, if confirmed in more diverse populations, GPBB could find utility as a stand-alone marker for identification of patients who may benefit from expedited confirmatory diagnostic investigation, particularly in those with small infarcts that typically present with minor, transient or equivocal symptoms.…”
Section: Discussionmentioning
confidence: 99%